The Unconstitutionality of the Offence of Insulting the Government in the 2023 Criminal Code: A Critical Review of Freedom of Expression - Yanis, Tryan Zaki Aulia; Muhtadi; Ahmad Saleh; M. Yanis, Adam (Universitas Islam Negeri Raden Intan Lampung, 2025)
The reintroduction of provisions on insulting the government in Articles 240 and 241 of Law No. 1 of 2023 has raised significant constitutional concerns, particularly given that similar provisions were previously annulled by the Constitutional Court in Decisions No. 013-022/PUU-IV/2006 and No. 6/PUU-V/2007. This study aims to analyze the rationale behind the reinstatement of these provisions and assess their constitutionality in light of the 1945 Constitution, especially regarding the right to freedom of expression. This study examines primary legal materials and relevant jurisprudence by employing a normative legal research method with conceptual, statutory, and case approaches. The findings show that the government justifies the provisions as social control tools based on insult as mala in se. However, their vague and subjective wording presents substantial risks of arbitrary interpretation, threatening democratic safeguards on criticism and free speech. The research concludes that despite procedural modifications, such as converting the offense into a complaint-based one, the substance of Articles 240 and 241 still contradicts constitutional guarantees and reflects a regression in legal protection for freedom of expression. This study highlights the urgency for more constitutionally aligned legislation and the role of the Constitutional Court as a guardian of democratic rights